Avian community composition affects ornithophilic mosquito and avian malaria turnover across an interfluvial system in southern Amazonia. (11th March 2021) - De La Torre, Gabriel M.; Campião, Karla M.; Bell, Jeffrey A.; Silva, Allan M.; Fecchio, Alan
Abstract : Determining the roles of host ecology and geography on the distribution of parasites is an important aim in disease ecology. However, this is extremely challenging for vector transmitted pathogens due to complex host–vector–parasite interactions. Here, we assess community turnover of birds, ornithophilic mosquitoes and Plasmodium parasites at different dimensions of diversity (taxonomic, functional and phylogenetic). We test if rivers can act as a geographic barrier to bird, mosquito and Plasmodium communities, and analyze the relationship among community turnover of these biological groups. We compiled two published datasets on bird, mosquito and Plasmodium communities collected in seven localities across the Tapajós river in southern Amazonia. We calculated the community turnover of bird, mosquito and Plasmodium communities, and identified the effect of river margin on community composition by comparing observed values with null models. Mantel tests were used to examine the different turnover dimensions within this host–vector–parasite system. Bird communities on the same riverbank were more similar, whereas bird phylogenetic turnover between riverbanks was more dissimilar than expected by chance. Neither mosquito nor Plasmodium turnover showed significant turnover between riverbank margins. We found a positive correlation between bird community turnover, both taxonomic and functional, and mosquito community turnover. Bird community taxonomic turnover was also positively related to Plasmodium community phylogenetic turnover. Our results suggest that geographic barriers created by the Tapajós river affect bird community assembly but do not constrain mosquito and Plasmodium distributions. Additionally, bird communities may play a key‐role in the community dynamics of mosquito vectors and Plasmodium parasites.